Development of an Autophagy-Based and Stemness-Correlated Prognostic Model for Hepatocellular Carcinoma Using Bulk and Single-Cell RNA-Sequencing - Shen, Shengwei; Wang, Rui; Qiu, Hua; Li, Chong; Wang, Jinghan; Xue, Junli; Tang, Qinghe (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence has proved that autophagy serves as a tumor promoter in formed malignancies and the autophagy-related prognostic signatures have been constructed as clinical tools to predict prognosis in many high mortality cancers. Autophagy-related genes have participated in the development and metastasis of HCC, but the understanding of their prognostic value is limited. Thereafter, LIMMA and survival analysis were conducted in both ICGC and TCGA databases and a total of 10 hub autophagy-related genes, involving NPC1, CDKN2A, RPTOR, SPHK1, HGS, BIRC5, SPNS1, BAK1, ATIC and MAPK3, were collected. Then, GO, KEGG, correlation, consensus and PCA analyses were utilized to reveal the potential targeted role of them in HCC treatment. Single cell RNA-seq of cancer stem cells also indicated that there was a positive correlation between these genes and stemness. In parallel, we applied uni-variate, LASSO and multi-variate regression analyses to study the autophagy-related genes and finally proposed that ATIC and BIRC5 were the valuable prognostic indicators of HCC. The signature based on ATIC and BIRC5 exhibited moderate power for predicting the survival of HCC in ICGC cohort and its efficacy was further validated in TCGA cohort. Taken together, we suggested that 10 aforementioned hub genes are promising therapeutic targets of HCC and the ATIC/BIRC5 prognostic signature is a practical prognostic indicator for HCC patients.